Extension of life span by down-regulation of enzymes catalyzing tryptophan conversion into kynurenine: Possible implications for mechanisms of aging. - Oxenkrug, G.; Navrotska, V. (Experimental biology and medicine (Maywood, N.J.), 2023)
The end products of catabolism of tryptophan (Trp), an essential amino acid, are known to affect mechanism(s) of aging, a neurodegenerative condition. This review focuses on the possible role of the initial step of Trp catabolism, kynurenine (Kyn) formation from Trp, in aging mechanism(s). Rate-limiting enzymes of Trp conversion into Kyn are tryptophan 2,3-dioxygenase 2 (TDO) or indoleamine 2,3-dioxygenase (IDO). Aging is associated with up-regulated production of cortisol, an activator of TDO, and pro-inflammatory cytokines, inducers of IDO. The other rate-limiting enzyme of Kyn formation from Trp is ATP-binding cassette (ABC) transporter that regulates Trp availability as a substrate for TDO. Inhibitors of TDO (alpha-methyl tryptophan) and ABC transporter (5-methyltryptophan) extended life span of wild-type Drosophila. Life span prolongation was observed in TDO knockdown of Caenorhabditis elegans and in TDO or ABC transporter-deficient Drosophila mutants. Down-regulation of enzymes catalyzing Kyn conversion into kynurenic acid (KYNA) and 3-hydroxykynurenine decreases life span. Considering that down-regulation of Methuselah (MTH) gene prolonged life span, aging-accelerating effect of KYNA, a GPR35/MTH agonist, might depend on MTH gene activation. Mice treated with TDO inhibitor, benserazide, an ingredient of anti-Parkinson medication carbidopa, and TDO-deficient Drosophila mutants were resistant to inducement of aging-associated Metabolic Syndrome by high-sugar or high-fat diets. Up-regulation of Kyn formation was associated with accelerated aging and increased mortality in human subjects. Trp-Kyn pathway is evolutionary conserved (from yeasts, through insects, worms, vertebrates to humans). Further studies might explore possible antiaging effect of down-regulation of Kyn formation from Trp by dietary, pharmacological, and genetic interventions.